Preliminary Report : Trace Elements Investigations in the Sweepstakes Creek Area, Koyuk District, Seward Peninsula, Alaska - Gault, H. Richard; Black, Robert F.; Lyons, John B. (Geological Survey (U.S.), 1946)
The following report provides information and findings of trace elements recognized in a few placer concentrates from Sweepstakes and Rube Creeks in the Koyuk district of eastern Seward Peninsula, Alaska when old collections were scanned for radioactivity in the spring of 1945.